2022
DOI: 10.3389/fpsyg.2022.793021
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Female Victims of Intimate Partner Violence: Systematic Review and Meta-Analysis

Abstract: Intimate partner violence (IPV) is an important problem that has significant detrimental effects on the wellbeing of female victims. The chronic physical and psychological effects of intimate partner violence (IPV) are complex, long-lasting, chronic, and require treatments focusing on improving mental health issues, safety, and support. Various psycho-social intervention programs are being implemented to improve survivor wellbeing. However, little is known about the effectiveness of different treatments on IPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 64 publications
2
13
0
5
Order By: Relevance
“…Patients’ average general self-efficacy scores at pretreatment were slightly lower than typically seen in IPV intervention studies [ 69 ], but at posttreatment, most patients’ general self-efficacy scores were above national US norms on this measure [ 70 ]. This is promising as several prior IPV intervention studies have demonstrated limited improvements in self-efficacy [ 69 , 71 ]. Additionally, patients’ average score was in the moderate range of depression at pretreatment and most of the patients reported no depressive symptoms or mild symptoms at posttreatment [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ average general self-efficacy scores at pretreatment were slightly lower than typically seen in IPV intervention studies [ 69 ], but at posttreatment, most patients’ general self-efficacy scores were above national US norms on this measure [ 70 ]. This is promising as several prior IPV intervention studies have demonstrated limited improvements in self-efficacy [ 69 , 71 ]. Additionally, patients’ average score was in the moderate range of depression at pretreatment and most of the patients reported no depressive symptoms or mild symptoms at posttreatment [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo realizado por Karakurt (2022), foi constatado que a depressão e o Transtorno de Estresse pós traumático são os diagnósticos mais comuns em casos de mulheres vítimas de violência doméstica, seguido por ansiedade. Vítimas de violência doméstica, que desenvolveram transtornos mentais não psicóticos, podem não receber o tratamento adequado, retornando outras vezes ao serviço.…”
Section: Discussionunclassified
“…Os programas de tratamento variam em seus objetivos, estruturas e abordagem principal, bem como métodos de entrega, como abrigos de violência doméstica, agências comunitárias de saúde mental e hospitais. Esses programas se baseiam em uma infinidade de modelos de terapia, como terapia cognitivo-comportamental (TCC), mindfulness, entrevista motivacional e escrita expressiva (Karakurt, et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A number of mental health concerns are associated with experiencing IPV, particularly PTSD, anxiety, substance abuse, and depression. These concerns often require treatment [91], which can be implemented with ongoing attention to physical and psychological safety. Particularly relevant to IPV are front-line trauma-focused PTSD psychotherapies, include cognitive processing therapy, prolonged exposure, and eye movement desensitization and reprocessing [113], as PTSD is among the most common conditions associated with IPV.…”
Section: Treat Mental Health Symptomsmentioning
confidence: 99%